Water-filling capacity and beamforming performance of MIMO systems with covariance feedback - Ming Kang; Alouini, M.-S. (2003 IEEE 4th Workshop on Signal Processing Advances in Wireless Communications, 2003)
The paper presents the exact moment generating function (MGF) of the water-filling capacity for the correlated MIMO Rayleigh fading channels with covariance feedback. This MGF result is then used to derive the capacity mean and variance as well as the outage capacity. We also derive the outage capacity and capacity mean as well as the outage probability and average bit error rate for the MIMO beamforming scheme with covariance feedback in a correlated Rayleigh fading environment.